Are biosimilars the next tool to guarantee cost-containment for pharmaceutical expenditures? - María-Isabel Farfan-Portet; Sophie Gerkens; Isabelle Lepage-Nefkens; Irmgard Vinck; Frank Hulstaert (2013)
Biological medicines contain a biological substance that is produced by or derived from a living organism. The active substances of biologicals are usually larger and more complex than those of chemically derived medicines (non-biological medicine). Biologicals are used for the treatment of chronic and life-threatening diseases such as cancer, multiple sclerosis and rheumatoid arthritis. Treatment with biologicals is usually expensive and represents ever-increasing pharmaceutical expenditures for the third-party payer.